Kepemimpinan Dalam Manajemen Pendidikan: Tinjauan Peran Kepala Sekolah Sebagai Manager - Fadila, Yosi; Yudistira, Srikandi; Hestivik, Chelsi; Hasri, Salfen; Sohiron, Sohiron (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this research is to see how school administrators function as managers in the context of educational management leadership. To improve educational standards in a time of rapid change, school principals musthavestrategicandadaptableleadershipskills. Literature review is the methodology used in thisresearch, where scholars collectan dexamine various related literary works, including books, scientific papers, and research reports. The analysis findings demonstrate the important role of administrators in creating a supportive schoolenvironment, motivating employees, and encouraging student engagement. This researchal sooutlines a number of good managerial techniques and leadership philosophies that can be used to achieve educational goals. Theseresults are expected to in crease perceptions regarding the importan ceo feducation